Johann Ludwig Langhansii legal document - Langhansii, Johann Ludwig
Sentence (1686 March 1) of twenty years given to Johann Ludwig Langhansii for corrupting the king of Bavaria.
Clergyman and prisoner.
Collection material in Latin.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bavaria (Germany) -- History -- 1180-1777.; Bavaria (Germany) -- Kings and rulers; Clergy; Prisoners